Syndecan-1: preditor de lesão renal aguda grave após cirurgia cardíaca pediátrica - Cavalcante, Candice Torres de Melo Bezerra (2016)
Background: Acute kidney injury (AKI) is common after pediatric cardiac surgery and is associated with adverse patient outcomes. Syndecan-1 is a biomarker of endothelial glycocalyx damage and its early increment after surgery can be associated with AKI. Objectives: evaluate Syndecan-1 and others biomarkers as predictors of severe AKI after pediatric cardiac surgery. Methods: Prospective cohort study with 289 patients less than 18 years old submitted to cardiac surgery at one reference institution. Postoperative plasma syndecan-1, intercellular adhesion molecule -1 (ICAM-1), e-selectine and neutrophil gelatinase-associated lipocalin (NGAL) were measured within the first 2 hours after cardiac surgery. Severe AKI –defined according Kidney Disease Improvement Global Outcome (KDIGO) stage 2 or 3- doubling of serum creatinine from the preoperative value or need for dialysis during hospitalization- was the main outcome. Analyses were adjusted for clinical variables for AKI risk stratification, including age, sex, preoperative estimated glomerular filtration rate, type of surgery, use of and cardiopulmonary bypass time longer than 120 minutes and “renal angina index” components - early decrease in estimated creatinine clearance from baseline and increase in % ICU fluid overload in the first day postoperative. Results: Plasma syndecan-1 measured early postoperative was independently associated with severe AKI. The accuracy of postoperative syndecan-1 for diagnosis of severe AKI was moderate (AUC-ROC of 0.77, 95% CI 0.68 – 0.85). The addition of syndecan-1 improved the discrimination capacity of a clinical model from 0.80 to 0.86 (p=0.004) and it also improved risk prediction as measured by net reclassification improvement (NRI) and integrated discrimination improvement (IDI). Postoperative sundecan-1 was also independently associated with longer length of ICU and hospital stay. N-GAL, e-selectine and I-CAM -1 were not associated with AKI and other outcomes. Conclusions: Postoperative plasma syndecan-1 is associated with subsequent severe AKI and poor outcomes among children undergoing cardiac surgery. It may be useful to identify patients who are at increased risk for AKI after cardiac surgery.